Changes of ongoing activity in Cebus monkey perirhinal cortex correlate with behavioral performance - B. Lima; M. Fiorani; R. Gattass (Brazilian Journal of Medical and Biological Research, 2005)
A Cebus apella monkey weighing 4 kg was trained in a saccadic eye movement task and while the animal performed the task we recorded the extracellular activity of perirhinal cortical neurons. Although the task was very simple and maintained at a constant level of difficulty, we observed considerable changes in the performance of the monkey within each experimental session. The behavioral states responsible for such variation may be related to arousal, motivation or attention of the animal while engaged in the task. In approximately 20% (16/82) of the units recorded, long-term direct or inverse correlations could be demonstrated between the monkey's behavioral state and the cells' ongoing activity (independent of the visual stimulation or of the specific behavior along a trial). The perirhinal cortex and other medial temporal structures have long been associated with normal memory function. The data presented here were interpreted in terms of recent reports focusing on the subcortical afferents to temporal lobe structures and their possible role in controlling arousal, motivation, or attention.